Propaganda: The challenges faced by journalists to protect media freedom in Albania - Stoica, Daniela-Carmen; Mirashi, Xhensila (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2025)
Propaganda has enmeshed the media in Albania. It has tuned it into a vassal that serves to convey a certain political agenda by convincing the masses through this unilateral conveyance of information. This brings about insecurity for free and independent journalists. For exemple, Citizen Channel, a nonprofit and independent media outlet, suffered a cyberattack in April 2024. At the same time, there is an inadequate approach to media education for Albanian citizens, especially the middle aged and the elderly. This study aims to identify the ideological impact of state-sponsored propaganda on the Albanian media, the challenges for journalists, and the audience’s media literacy and willingness to engage in fact-checking. To achieve this goal, qualitative and quantitative methods were used by monitoring four national media outlets, as well as using questionnaires as a measuring instrument for journalists.